The effectiveness of clinical problem-based learning model of medico-jurisprudence education on general law knowledge for Obstetrics/Gynecological interns - Hui-Chin Chang; Ning-Yen Wang; Wen-Ru Ko; You-Tsz Yu; Long-Yau Lin; Hui-Fang Tsai (Elsevier, 2017)
Objective: The effective education method of medico-jurisprudence for medical students is unclear. The study was designed to evaluate the effectiveness of problem-based learning (PBL) model teaching medico-jurisprudence in clinical setting on General Law Knowledge (GLK) for medical students. Materials and methods: Senior medical students attending either campus-based law curriculum or Obstetrics/Gynecology (Ob/Gyn) clinical setting morning meeting from February to July in 2015 were enrolled. A validated questionnaire comprising 45 questions were completed before and after the law education. Results: The interns attending clinical setting small group improvisation medico-jurisprudence problem-based learning education had significantly better GLK scores than the GLK of students attending campus-based medical law education course after the period studied. Conclusion: PBL teaching model of medico-jurisprudence is an ideal alternative pedagogy model in medical law education curriculum.